Forever Ramón Viladot - Herrera-Perez, Mario (Journal of the Foot & Ankle, 2022)
Dear colleagues and friends of the Latin American Foot and Ankle world, it is for me an honor and at the same time a great sadness to pass along the sad news that January brought to all of us. Ramón Viladot-Pericé, world reference in Foot and Ankle and professor of generations of specialists in Spain and Latin America, passed away in Barcelona. Providence wanted that, in the last months and even years, we had been united by an intense research activity, and I have the honor of having published with him his last scientific article, published last year in this scientific journal. What can we say… we have plenty of reasons to highlight his impressive scientific legacy and even more reasons to stress his unmeasurable human qualities. His absence leaves an enormous void impossible to fill. From the scientific point of view, his last moments were filled with an unprecedented resurgence of science in all senses: it was not time to end a project to start another, and the hours and days were not enough to meet his goals. Perhaps he never thought of such a hasty end, but even so, destiny prepared him to say goodbye in the best way: communicating how much he knew about Foot and Ankle. Among many other things, I am left with the calls of the last months, full of affection and cognizance of the perfection of his work, but also with his inexhaustible eagerness for rigorous scientific production. With Ramón Viladot part of the History of Foot and Ankle is gone. Probably nothing will be the same from now on, but we are left with his unequaled personal and scientific legacy, his disposition, his human qualities. Surely many of the readers of this Editorial can identify with these words, as there are many of us who have shared operations and consultations with him both at the Hospital San Rafael and at the Clínica Tres Torres in Barcelona. The person died, but the memory lives on. As writer Mario Benedetti said: “If I live in your memory, I will not be alone.” We will all certainly remember him forever. Forever Ramón...